Effects of oral administration of sodium citrate or acetate to pigs on blood parameters, postmortem glycolysis, muscle pH decline, and quality attributes of pork - Stephens, J.W.; Dikeman, Michael E.; Unruh, John A.; Haub, M.D.; Tokach, Michael D.; Dritz, Steven S. (My University, 2008)
The objective of this study was to determine the effects of oral administration of sodium citrate (CIT) or acetate (ACE) to pigs on blood parameters, postmortem glycolysis, pH decline, and quality attributes of pork. Previous studies have shown that CIT has the potential to inhibit phosphofructokinase (PFK), a key enzyme in postmortem muscle glycolysis. In Exp. 1, CIT, ACE, or water was orally administered (0.75 g/kg of BW) to 24 pigs. After a 30-min rest, pigs were exercised, and blood samples were taken at 45 and 75 min after oral treatment. Citrate and ACE tended (P = 0.08) to increase blood pH and increased (P = 0.02) bicarbonate levels immediately after exercise. After a 30-min rest, blood pH of pigs administered ACE tended (P = 0.09) to remain higher, whereas blood pH of CIT-treated pigs was similar to that of control pigs. Bicarbonate levels in ACE- and CIT-treated pigs were still greater (P < 0.05) than those of control pigs at 75 min after oral treatment. In Exp. 2, 30 pigs were administered CIT, ACE, or water 45 min before stunning (electric plus captive bolt). Antemortem treatments had no effect (P > 0.10) on muscle pH or postmortem concentrations of the glycolytic metabolites of glucose-6 phosphate, fructose-6 phosphate, fructose-1,6 bisphosphate, glyceraldehyde-3 phosphate, dihydroxyacetone phosphate, or lactate. Minor, but inconsistent, differences in quality attributes were found in LM chops, and no differences in quality attributes were found between control and CIT- or ACE-treated pigs for inside and outside semimembranosus muscles (P > 0.10). There was no significant inhibition of the PFK enzyme by orally administered CIT or ACE; however, the PFK glycolytic metabolite data analysis indicated that PFK was a main regulatory enzyme in postmortem muscle.
Keywords: Meat quality; Pork; Glycolysis; Citrate; Acetate